Interactions between nascent proteins translated by adjacent ribosomes drive homomer assembly - Bertolini, Matilde; Fenzl, Kai; Kats, Ilia; Wruck, Florian; Tippmann, Frank; Schmitt, Jaro; Auburger, Josef Johannes; Tans, Sander; Bukau, Bernd; Kramer, Günter (Science, 2021)
Co-co assembly for oligomers - Most of the human proteome forms oligomeric protein complexes, but how they assemble is poorly understood. Bertolini et al. used a ribosome-profiling approach to explore the existence of a cotranslational assembly mode based on the interaction of two nascent polypeptides, which they call the “co-co” assembly. Proteome-wide data were used to show whether, when, and how efficiently nascent complex subunits interact. The findings also show that human cells use co-co assembly to produce hundreds of different homo-oligomers. Co-co assembly involving ribosomes translating one messenger RNA may resolve the longstanding question of how cells prevent unwanted interactions between different protein isoforms to efficiently produce functional homo-oligomers. - Science, this issue p. 57 - Structured Abstract - INTRODUCTIONMost newly synthesized proteins associate into macromolecular complexes to become functional. Complex formation requires that subunits find each other in the crowded cellular environment while avoiding unspecific interactions and aggregation.Recent findings indicate that native complex formation is facilitated by coupling protein synthesis by ribosomes (translation) with folding and assembly. Studies analyzing formation of heteromeric complexes have elucidated the cotranslational engagement of nascent subunits by their fully translated, diffusing partner proteins (co-post assembly). We considered an alternative assembly mechanism that involves the interaction of two nascent subunits during their concurrent translation (co-co assembly) and thereby uncouples assembly from subunit diffusion. Provided that the interacting subunits are synthetized on one polysome, co-co assembly would increase the fidelity of homomer formation, prevent non-specific interactions with structural homologs and isoforms, and facilitate spatial and temporal coordination of the process. Whether cells employ co-co assembly as a general strategy for complex assembly, when and how efficiently nascent subunits interact, and what mechanisms are driving the process remain unclear. - RATIONALEUpon co-co assembly, single translating ribosomes (monosomes) become connected via nascent proteins. These ribosome pairs (disomes) persist during nuclease treatment of cell lysates and protect mRNA fragments of 30 nucleotides in length (ribosome footprints). Our approach relies on the different sucrose gradient sedimentation properties of disomes and monosomes. Sequencing of footprints isolated from monosome and disome fractions identifies co-co assembly candidates across the nascent proteome as the mRNAs on which ribosomes shift from the monosome to the disome fraction during translation [disome selective profiling (DiSP)]. The position of the shift defines the co-co assembly onset and reveals exposed nascent protein segments that mediate dimerization. - RESULTSWe employed DiSP to reveal comprehensive information about the co-co assembling proteome of two human cell lines and mechanistic principles of the assembly process. Interactions between nascent subunits are highly prevalent, involving thousands of candidate proteins from different cellular compartments. Co-co assembly is mostly employed to form homomeric rather than heteromeric complexes and is generally correlated with the exposure of N-terminal dimerization interfaces. Five conserved structural motifs are the main drivers of co-co assembly; among these, coiled coils are most prevalent, followed by BTB, BAR, SCAN, and RHD domains.Reconstitution in bacteria revealed that this process can occur independent of dedicated, eukaryote-specific assembly factors and minimally relies on the dimerization propensity of nascent protein N termini.Finally, we monitored the composition of lamin dimers inside human cells and showed that homodimer-forming subunits are templated by one transcript. This observation implies that cells may generally employ co-co assembly on a polysome to avoid mixing isoforms that share identical dimerization domains. - CONCLUSIONOur study shows a previously unrecognized level of coupling of protein synthesis with complex assembly and provides direct evidence for the widespread occurrence of cotranslational interactions between nascent subunits in human cells. We propose that the polysome constitutes the platform for most co-co assembly interactions. This enhances the efficiency and accuracy of homomer formation and enables cells to independently evolve functionally diverse homomeric protein complexes that use recurrent oligomerization domains. Download high-res image Open in new tab Download Powerpoint Disome selective profiling reveals proteome-wide interactions between nascent proteins.Ribonuclease treatment of human cell lysates generates monosomes (M) and nascent protein-connected disomes (D) that are purified by sucrose gradient centrifugation. Ribosome-protected footprints from both fractions are deep-sequenced. A shift of elongating ribosomes from the monosome to the disome fraction indicates co-co assembly. The mRNA position of the shift reveals the dimerization motif that mediates assembly. Abs, absorbance; nt, nucleotides. - Accurate assembly of newly synthesized proteins into functional oligomers is crucial for cell activity. In this study, we investigated whether direct interaction of two nascent proteins, emerging from nearby ribosomes (co-co assembly), constitutes a general mechanism for oligomer formation. We used proteome-wide screening to detect nascent chain-connected ribosome pairs and identified hundreds of homomer subunits that co-co assemble in human cells. Interactions are mediated by five major domain classes, among which N-terminal coiled coils are the most prevalent. We were able to reconstitute co-co assembly of nuclear lamin in Escherichia coli, demonstrating that dimer formation is independent of dedicated assembly machineries. Co-co assembly may thus represent an efficient way to limit protein aggregation risks posed by diffusion-driven assembly routes and ensure isoform-specific homomer formation. - Co-co assembly during protein synthesis provides an efficient mechanism to limit aggregation risks during homomer formation. - Co-co assembly during protein synthesis provides an efficient mechanism to limit aggregation risks during homomer formation.